Dithienylethene-containing cyclic and linear conjugated molecules: Synthesis, photochromism, and photoluminescence. (November 2021) - Lin, Yen-Jen; Horie, Masaki
Abstract: Cyclic and linear conjugated small molecules comprising dithienylethene (DTE) and thiophene groups were synthesized via Suzuki and McMurry couplings. The cyclic molecule was polymerized via ring-opening metathesis polymerization (ROMP) using a second-generation Grubbs catalyst to produce a DTE- and thienylene vinylene-containing conjugated polymer. DTE-containing small molecules exhibited (quasi-) reversible photochromism through alternating UV and visible light irradiation. The small linear molecules showed faster photochromism than the cyclic molecule. In contrast, the linear dimer and polymer did not undergo photochromism; however, they showed efficient photoluminescence, with quantum yields of 0.26 and 0.18, respectively. Graphical abstract: Image 1